1983
DOI: 10.1159/000183003
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthesis from Serine in Isolated Perfused Hindquarters of Acutely Uraemic Rats

Abstract: Isolated hindquarters of bilaterally nephrectomized and sham-operated rats were perfused in the presence and absence of 14C-labelled serine, respectively. After a perfusion period of 30 min 14C-serine was 4,074 ± 270 dpm/ml in the perfusion medium of sham-operated animals and decreased to 2,800 ± 190 dpm/ml in the medium of acutely uraemic rats. Muscle glycogen concentration in sham-operated animals was 1.10 ± 0.04 mg/g wet weight in the absence and 1.03 ± 0.11 mg/g in the presence of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In agreement with previous observations there was a decrease of blood lactate and pyruvate concentrations following bilateral nephrectomy [20] (tables III, IV). Therefore, the ratio of lactate to pyruvate -a possible indicator of the redox state of the tissues -remained constant.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous observations there was a decrease of blood lactate and pyruvate concentrations following bilateral nephrectomy [20] (tables III, IV). Therefore, the ratio of lactate to pyruvate -a possible indicator of the redox state of the tissues -remained constant.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, some substrates other than glycine must be considered as precursors of serine. Several studies have shown a key role of serine in liver and skeletal muscle metabolism of acutely uremic rats [3][4][5][15][16][17][18][19][20], Fortunately, extrarenal serine synthesis may prevent serine deficiency even fol lowing bilateral nephrectomy.…”
Section: Discussionmentioning
confidence: 99%